Risk factors and outcomes, a case series of ischemic stroke in children - Shirley L. Anggriawan; lrawan Mangunatmadja; Djajadiman Gatot; Sofyan lsmael; Najib Advani (Indonesian Pediatric Society, 2009)
Ischemic strokes in children, although generallyrare events, are more prevalent than commonlybelieved. Ischemic stroke in children have beenassociated with coagulation disorders, cardiacanomalies, infections and trauma.